Pedagogy around graffiti - Bogusław Śliwerski (Studia z Teorii Wychowania)
In this article graffiti is perceived as the art of living with images operated by young artists. The author draws attention to the fact that this art does not only have a negative perception of character, and thus also a social perception (reception). There is explained what the polarization effect of two neighboring generations of graffiti artists in the social space is - open and hidden, in which a presented group of artists tries to manifest their position and presence. Is it worth talking about graffiti in pedagogy in social sciences? The author analyzes it (graffiti) which may not penetrate the structures of life of the young generation, their school, and out-of-school environments, and what does not become the source of rebellion and also a way for establishing a new type of social and educational relationship.